Evaluation of Early Neuro-Imaging Requests for Dementia Diagnosis in Wolverhampton Memory Assessment Service (MAS). (June 2022) - Prasanna, Aparna; Mandair, Kuljit; Ling, Clare
Abstract : Aims: The Wolverhampton Memory Assessment Service (MAS) is nurse led and accepts referrals from primary and secondary care settings. There has been a rapid rise in the number of referrals as well as an increase in demand to provide a timely diagnosis. This poses a challenge to meet the national aspiration of referral to diagnosis in 6 weeks. The aim is to improve access to neuroimaging in order to avoid delays to diagnosis and management. Methods: In January 2022, a retrospective sample of three groups of newly referred patients to MAS between 1st June-31st October 2021 was selected, each group consisting of 15 patients. A dedicated tool was used to collect data. MAS follows NICE standards for neuroimaging in dementia guidance. In Group 1 scans were not requested at referral but were requested after initial nursing assessment, in Group 2 scans were available at initial referral and in Group 3 scans were requested by the MAS Consultant Psychiatrist upon receipt of referral. Results: In group 1; 47% of patients have still not had a scan (with a waiting time of approximately 6 months) and 73% have not been given a diagnosis. Three patients were given a diagnosis due to exceptional circumstances and therefore the results of these patients can be disregarded. In group 2, all (100%) patients had a scan either prior to the referral (73%) or requested by GPs at the time of referral (27%). 80% of patients have been given a diagnosis. The average days from referral to diagnosis was 82 days. Patients not given a diagnosis yet was due to cancellation/awaiting appointments. In group 3, all (100%) patients have had a scan and 67% of patients have been given a diagnosis. The average days from referral to diagnosis was 102 days. Patients not given a diagnosis yet was due to cancellation/awaiting appointments. Conclusion: Implementing a pathway whereby clinicians can either have access to prior neuroimaging or refer appropriate patients for scans at the point of referral, significantly reduces waiting times to diagnosis and management within a timely manner. This reduces carer burden and provides increased support from appropriate services as well as reducing the chances of patients ending up on crisis pathways. There is a need to implement an integrated care pathway that is responsive and accessible to all patients.